Effectiveness of Biology E-Module Teaching Materials Based on Flip Pdf Professional Application to Improve Learning Outcomes and Critical Thinking Skills - Eka Fitria Purnamasari; Elsje T. Maasawet; Yusak Hudiyono; Lambang Subagiyo; Herliani; Akhmad (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to develop e-module teaching materials that can be used by teachers and students both in school and outside school by developing one of the Plip Pdf Professional applications as an innovation media in a fun learning process. The type of research used is research and development (R&D). The sample in this study were biology teachers and students of SMA Negeri 5 Samarinda and SMA Negeri 11 Samarinda. The results of the expert validation of the teaching materials produced were very good with an average score of 3 validators of 91.33% with the category (very valid). The practicality of the teaching materials assessment from the teacher showed a result of 95.31% (very practical), while the assessment from students got a score of 89.06% (very practical). The effectiveness of the teaching materials produced was able to provide an increase in cognitive learning outcomes with a gain score index of 0.83 (high) and the percentage value of students' critical thinking skills was 88.8%. The results of the effectiveness test using the paired sample t-test showed that there was an influence of the use of e-module teaching materials based on the Plip Pdf Professional application in improving the biology learning outcomes of students at SMA Negeri 5 and SMA Negeri 11 Samarinda on the Human Respiratory System material.